Science, Religion, Government, and SARS-CoV-2: A Time for Synergy - Hong, Barry A. (Journal of religion and health, 2020)
Religion, science and government have been institutions throughout the ages that have helped us deal with fears and threats like SARS-CoV-2. However, reliance on any one of these institutions exclusively has limitations and therefore are sources of disappointments. The SARS-CoV-2 is a reminder that we can and need to blend these seemingly divergent views of science, religion and government. Each of these institutions provides ways to cope with this worldwide pandemic but they can exercise a much greater impact if they operate in unison for the common good and well-being of all.